Siegfried Kracauer and Weimar culture: modernity, flânerie, and literature - Fleischer, Ulrike (2001)
This thesis is concerned with Siegfried Kracauer’s response to the challenges of modernity as exemplified by the Weimar Republic and its culture. A consideration of the literary dimension of Kracauer’s work is a central aspect of my approach. Beginning with a brief examination of Kracauer s early, epistemological writings, which adopt an anti-modem tone, my thesis then examines his shift towards a materialist critique of modernity. Using his essay 'Das Ornament der Masse' as a key example, I argue that Kracauer assumes the stance of a flâneur vis-à-vis the culture he examines. While this is consistent with his role as a Feuilleton journalist, the flâneur's detachment compromises Kracauer's political position. Here, and throughout the thesis, Kracauer's narrative approach and its effects are drawn out through comparisons with contemporary literary texts. In the remaining three chapters of my thesis, I analyse the novels Ginster and Georg, as well as the sociological study Die Angestellten. Here, I suggest, Kracauer attempts to transcend the limitations imposed by the flâneur's detachment. In Ginster he critically reflects on his own personal and political development while Die Angestellten is an attempt at social intervention. In Georg, finally, Kracauer returns to exploring crucial factors of Weimar (political) culture and considers his own role, as a journalist, within them.